Bioengineering of a CLiP‐derived tubular biliary‐duct‐like structure for bile transport in vitro. Issue 7 (3rd May 2021) - Huang, Yu; Sakai, Yusuke; Hara, Takanobu; Katsuda, Takeshi; Ochiya, Takahiro; Gu, Wei‐Li; Miyamoto, Daisuke; Hamada, Takashi; Hidaka, Masaaki; Kanetaka, Kengo; Adachi, Tomohiko; Eguchi, Susumu
Abstract: The integration of a bile drainage structure into engineered liver tissues is an important issue in the advancement of liver regenerative medicine. Primary biliary cells, which play a vital role in bile metabolite accumulation, are challenging to obtain in vitro because of their low density in the liver. In contrast, large amounts of purified hepatocytes can be easily acquired from rodents. The in vitro chemically induced liver progenitors (CLiPs) from primary mature hepatocytes offer a platform to produce biliary cells abundantly. Here, we generated a functional CLiP‐derived tubular bile duct‐like structure using the chemical conversion technology. We obtained an integrated tubule‐hepatocyte tissue via the direct coculture of hepatocytes on the established tubular biliary‐duct‐like structure. This integrated tubule‐hepatocyte tissue was able to transport the bile, as quantified by the cholyl‐lysyl‐fluorescein assay, which was not observed in the un‐cocultured structure or in the biliary cell monolayer. Furthermore, this in vitro integrated tubule‐hepatocyte tissue exhibited an upregulation of hepatic marker genes. Together, these findings demonstrated the efficiency of the CLiP‐derived tubular biliary‐duct‐like structures regarding the accumulation and transport of bile. Abstract : The integration of a bile drainage system into engineered liver tissue was successfully performed via the direct coculture of hepatocytes on the chemically induced liver progenitors (CLiPs)‐derived tubular biliary‐duct‐like structure. The integrated tubule‐hepatocyte tissue was able to transport the bile, as quantified by the Cholyl‐Lysyl‐Fluorescein (CLF) assay. These results were highlighting the possibility of the establishment of a system that supports the interaction between the hepatocytes and the biliary‐duct‐like structure for the accumulation of the bile acid analog in vitro.